Zebrafish Exploit Visual Cues and Geometric Relationships to Form a Spatial Memory - Ksenia Yashina; Álvaro Tejero-Cantero; Andreas Herz; Herwig Baier (iScience, 2019)
Summary: Animals use salient cues to navigate in their environment, but their specific cognitive strategies are largely unknown. We developed a conditioned place avoidance paradigm to discover whether and how zebrafish form spatial memories. In less than an hour, juvenile zebrafish, as young as 3 weeks, learned to avoid the arm of a Y-maze that was cued with a mild electric shock. Interestingly, individual fish solved this task in different ways: by staying in the safe center of the maze or by preference for one, or both, of the safe arms. In experiments in which the learned patterns were swapped, rotated, or replaced, the animals could transfer the association of safety to a different arm or to a different pattern using either visual cues or location as the conditioned stimulus. These findings show that juvenile zebrafish exhibit several complementary spatial learning modes, which generate a flexible repertoire of behavioral strategies. : Biological Sciences; Behavioral Neuroscience; Evolutionary Biology Subject Areas: Biological Sciences, Behavioral Neuroscience, Evolutionary Biology